Manajemen Pendidikan Mental di Madrasah Aliyah Plus Nururrohmah Tambaksari Kecamatan Kuwarasan Kabupaten Kebumen - Suharti Suharti (LPPM IAINU Kebumen, 2019)
The success of mental education in schools/madrasas is determined by its management, especially mental education management. Management of mental education is a planned effort to make students confident, brave, mentally strong and internalize values ​​so that students are able to grow their distinctive mentality which consists of planning, organizing, implementing and supervising processes. Madrasah Aliyah Plus Nururrohmah Tambaksari Kuwarasan Kebumen is a private secondary formal education institution under the auspices of the Ministry of Religion in Kebumen Regency. The purpose of this study was to determine the management of mental education at Madrasah Aliyah Plus Nururrohmah Tambaksari Kuwarasan Kebumen. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. The data collected from these techniques were analyzed using data reduction, data presentation, and verification (conclusion). Based on the results of the analysis, it can be found that the implementation of mental education at Madrasah Aliyah Plus Nururrohmah Tambaksari Kuwarasan Kebumen is carried out in every school/madrasah activity through: (1) learning activities, (2) extracurricular activities, and (3) habituation activities. Mental Education Management at Madrasah Aliyah Plus Nururrohmah Tambaksari Kuwarasan Kebumen consists of: (1) mental education planning; (2) organizing mental education; (3) implementation of mental education; and (4) supervision of mental education. Planning for mental education includes: (1) at the beginning of a new school year; (2) based on the school's vision and mission; (3) compiling programs; (4) disseminated to madrasa residents; (5) mental values ​​are integrated into lesson plans; (6) compiling extracurricular activity programs and habituation activities. Organizing mental education includes: (1) division of tasks for teachers who handle learning; (2) division of tasks for supervising teachers for extracurricular activities; (3) form the person in charge of habituation activities. The implementation of mental education includes: (1) learning activities; (2) extracurricular activities; (3) habituation activities. Supervision of mental education includes: (1) involving all components of the school; (2) observing the behavior of students; (3) working with teachers, homeroom teachers, Counseling (BK) teachers, and parents to monitor students' mental development.